2019
DOI: 10.1016/j.jvolgeores.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Water and dissolved gas geochemistry at Coatepeque, Ilopango and Chanmico volcanic lakes (El Salvador, Central America)

Abstract: Coatepeque (on the E slope of Santa Ana Volcano), Ilopango (inside Ilopango Caldera) and Chanmico (associated with San Salvador Volcano) are volcanic lakes in El Salvador, showing a thermocline at a relatively shallow depth (from 30 to 40 m, from 20 to 40 m and from 5 to 15 m depth, respectively) and anoxic conditions below 33, 24 and 4 m depth, respectively. The Na +-Cl − composition of the Coatepeque and Ilopango lakes, displaying TDS values up to 1226 and 1216 mg/L, respectively, is likely due to hydrotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 86 publications
1
3
0
2
Order By: Relevance
“…The irregular shape of the 3 km-wide collapse caldera and its crater lake is in agreement with the presumed young age of the crater and the latest magmatic eruption (<1 ka; Fontijn et al, 2010). A pioneering study on the water chemistry of Lake Ngozi (Delalande-Le Mouëllic et al, 2015) hypothesizes that the lake is affected by geothermal input (Na-Cl-rich, Mg-poor) and hydrothermal activity (pH 6.4-6.9, SO 4 -rich steam heated waters), similar to the caldera lakes in El Salvador (Cabassi et al, 2019;Rouwet, 2021). Dominant CO 2 degassing (δ13C-DIC from +2.8 to +5.8‰, Delalande-Le Mouëllic et al, 2015) is probably of magmatic origin as also suggested by the high 3 He/ 4 He ratios (7-8.3 Ra, de Moor et al, 2013).…”
Section: Tanzaniasupporting
confidence: 63%
“…The irregular shape of the 3 km-wide collapse caldera and its crater lake is in agreement with the presumed young age of the crater and the latest magmatic eruption (<1 ka; Fontijn et al, 2010). A pioneering study on the water chemistry of Lake Ngozi (Delalande-Le Mouëllic et al, 2015) hypothesizes that the lake is affected by geothermal input (Na-Cl-rich, Mg-poor) and hydrothermal activity (pH 6.4-6.9, SO 4 -rich steam heated waters), similar to the caldera lakes in El Salvador (Cabassi et al, 2019;Rouwet, 2021). Dominant CO 2 degassing (δ13C-DIC from +2.8 to +5.8‰, Delalande-Le Mouëllic et al, 2015) is probably of magmatic origin as also suggested by the high 3 He/ 4 He ratios (7-8.3 Ra, de Moor et al, 2013).…”
Section: Tanzaniasupporting
confidence: 63%
“…Therefore, limited risk of limnic eruptions is assumed, though monitoring measures are advised as sudden CO 2 recharge 12 due to renewed or increased gas input cannot be excluded. In that context Lake Ngozi is rather comparable to the geothermally heated Kelud crater lake (Indonesia) 13 or volcanic lakes in El Salvador 14 , than Lake Nyos, Lake Kivu or Lake Monoun.…”
Section: Introductionmentioning
confidence: 92%
“…El lago de Coatepeque (13º 51' 48.0" N, -89º 32' 45.9" W) abarca 25.3 km 2 de superficie acuática y su origen está asociado al colapso de un antiguo volcán (Cabassi et al, 2019). La cuenca de este cuerpo de agua es endorreica (Quiñonez-Basagoitia, 2019) y se ubica entre los departamentos de Sonsonate y Santa Ana en la zona oeste del país, aproximadamente a 740 metros sobre el nivel del mar.…”
Section: Materiales Y Método Sitiounclassified